MLVA-TYPINGIN THE ANALYSIS of THE POPULATION STRUCTURE of VIBRIO CHOLERAE, CIRCULATING IN PRIMORSKY KRAI TERRITORY, DURING EPIDEMIOLOGICAL WELFARE - Z. Y. Khunkheeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
In order to study the population structure of Vibrio cholerae, circulating in the waters of Primorsky Region territory during epidemiological welfare, was carried out a retrospective MLVA-typing of 50 V.cholerae strains isolated since 1976 up to 2011 years. There was revealed non-toxigenic V. cholerae strains heterogeneity, consisting in the variability of structure of these tandem repeat loci. The waters circulation of Primorsky Region territory during epidemiological welfare V.cholerae, submitted by no less than 30 unique genotypes and 8 clusters is represented. There is a high discriminatory power of the MLVA. The Hunter Gaston index of isolates studied is 0.988. In some cases, was revealed relationship between genotype (identical and closely related allelic profiles) with time and place of V.cholerae strains isolation.